Complexidade e metodologia de projetos: melhorando a pratica docente em cursos de graduação tecnológica - Prado, Fernando Leme do (2007)
The focus of the present work is project methodology specifically, the methodology of integrating projects such as practiced by the College of Technology Professor Luiz Rosa , in Jundiaí, State of São Paulo, Brazil. Its objective is to reflect about the teaching practices adopted in the undergraduate programs in technology offered by that institution. Reflection is conducted in the light of the guiding principles of action research, in one of its variants, known as Investigación-Acción (Carr e Kemmis,1988; MacTaggart, 1988; e Latorre 2003). The strategies of this variant are non-cartesian, and, therefore, better applicable to non-linear systems. The question of which pedagogical practices are most appropriate to the programs in technology offered by the institution, given the competencies and skills that the social and productive environment requires today, is the starting-point of this reflection. It is proposed, in answer to this question, that an analysis of the procedures adopted by the actors involved in the projects (students, professors and coordinators of different academic areas and disciplines) can, when guided by theoretical frameworks open to uncertainty, unveil the principles of a complex methodology that can be applied, with good results, to any programs of technology. The present study, based on the tools of action research and on the theoretical assumptions of the General Systems Theory (Bunge and Vieira), of the eco-systemic paradigm (Moraes) and of the theory of complex thought (Morin), has shown that project methodologies evolved from interdisciplinary projects (first phase) into integrating projects (second phase), and, presently, show a tendency to move into a third phase, still under construction, named bureau of integrating projects. The present phase has shown a significant increase in the organization and complexity, both of the institution offering the projects and of the methodology used, when and if open, non-linear systems are considered